An efficient computational scheme for robot manipulators - Tenreiro Machado, J. A. (2019)
A new robot manipulator computational scheme which is a blend of ordinary and Boolean algebra is presented. This method may also be interpreted as a dedicated compiler that optimizes the on-line computing time at expenses of the off-line stage. The off-line requirements are alleviated, by the implementation of some general rules that stem from the structure of the robot manipulator equations, and the on-line computing time is optimized through the use of Binary Decision Diagrams. The results show a considerable computational improvement on conventional sequential machines but, furthermore, they clearly point out new computational parallel architectures. Finally, it is observed that the proposed algorithm is not restricted to robot dynamic computations, but is also applicable to many other computing structures.